Quality parameters and consumer acceptance of pomegranate carrot jelly - Likhitha, P Sree; Swetha, G; Niharika , M (Journal of Postharvest Technology, 2023)
Pomegranate is (Punica granatum) a long lived and drought-tolerant plant. They are widely cultivated in India, Iran and Mediterranean countries. Pomegranate can help to prevent or treat various disease risk factors such as High Blood Pressure, High Cholesterol, Oxidative Stress and Hyperglycemia. The Pomegranate fruits are used to prepare Jellies, Candies, Juices, Salads, Smoothies and Yogurt. The present Study is aimed to develop Pomegranate Carrot Jelly. Carrot is included in this product due to increase of beta-carotene. Carrot’s area unit made in vitamins, minerals and fiber. They are additionally a decent supply of antioxidants. Carrots may reduce the risk of cancer and support cholesterol balance & heart health. The Jellies are made with different proportion of ingredients like Pomegranate, Carrot, Sugar, Gelatin & Cardamom. The Jellies are developed in 3 variations, these variations are evaluated by panel members with organoleptic methods. According to the organoleptic evaluation results the variation-3 was good. It was concluded that pomegranate is a medicinal fruit and they can include it in their diets could be benefits for good health.